Intrahepatic Cholestasis of Pregnancy and Associated Adverse Maternal and Fetal Outcomes: A Retrospective Case-Control Study - Mingjuan Luo; Mengyang Tang; Feng Jiang; Yizhen Jia; Robert Kien Howe Chin; Wei Liang; Hu Cheng (Gastroenterology Research and Practice)
Objective. Intrahepatic cholestasis of pregnancy (ICP) is a common pregnancy-related liver disease and is associated with an increased risk of adverse neonatal outcomes. Ursodeoxycholic acid (UDCA) is the most effective treatment. This study was aimed at investigating the adverse outcomes of ICP and evaluating the effects of treatment with UDCA in patients with ICP. Methods. We included 114 women with ICP and 3725 women without ICP (no-ICP group) who delivered in our hospital between September 2017 and August 2019. The prevalence of ICP in this study was 3.15%. We matched each woman with ICP to five controls. Of all the 114 women with ICP, 73 (64.04%) received UDCA while 41 (35.96%) did not. Logistic multivariate regression analysis was used to compare the adverse outcomes between those with ICP and matched controls as well as between those who received UDCA (UDCA group) and those who did not (non-UDCA group). Results. Compared with controls, women with ICP were more likely to have preeclampsia (adjusted odds ratio, aOR=16.74, 95% CI 5.29–52.98), cesarean section (aOR=1.76, 95% CI 1.10–2.81), and preterm birth (aOR=24.35, 95% CI 2.74–216.67). Administration of UDCA reduced the rate of preterm birth (1.37% vs. 14.63%, aOR=0.10, 95% CI 0.01–0.90). Conclusion. ICP increased the risk of preeclampsia, cesarean section, and preterm birth. UDCA could reduce the rate of preterm birth.